Chrysoperla carnea Stephens (Chrysopidae: Neuroptera) - a potential biocontrol agent of cardamom aphid (Pentalonia nigronervosa f. caladii van der Goot) - Venugopal, M J Mathew, K A Saju, M N (Journal of Spices and Aromatic Crops, 1998)
Viral diseases such as mosaic (katte) and vein clearing disease (kokke kandu) of cardamom (Elettaria cardamomum Maton) are transmitted by the cardamom aphid (Pentalonia nigronervosa f. caladii van der Goot) (Homoptera: Aphididae). Insecticides are ineffective in controlling the aphids since their colonies are found in the concealed senile parts of the host and also due to their hyperactivity and subsequent migration and probing to other plants on exposure to insecticides (Raj an et al. 1989) which might further increase the spread of the disease.